Evaluasi Kelayakan Ekonomi Pembangunan Jembatan Kali Sorong Menggunakan Metode Cost Benefit Analysis (CBA) - Nadia Adawi Hidayatunnisa; Fedya Diajeng Aryani; Baiq Virgia Srihayati (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The construction of the Kali Sorong Bridge aims to improve accessibility and support the smooth mobility of the community. Prior to project implementation, an economic feasibility evaluation is required to assess the balance between the expected benefits and the investment costs incurred. This study aims to evaluate the economic feasibility of the Kali Sorong Bridge construction using the Cost Benefit Analysis (CBA) method with the indicators of Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). The benefit components analyzed include travel time savings, travel cost savings, improved safety and comfort, reduced traffic congestion, and regional economic development. The cost components consist of land acquisition costs, planning costs, construction costs, and maintenance costs. The analysis results show a BCR value of 1.373, an NPV of –IDR 794,410,335, an IRR of 2.46%, and a Payback Period of 19 years and 7.07 months. The BCR value indicates that the project's benefits exceed its costs, whereas the NPV and IRR values indicate that the project does not satisfy the feasibility criteria based on these two indicators. Therefore, the economic feasibility assessment of bridge construction projects should consider all evaluation indicators comprehensively to support more informed investment decisions.